Assessment of Ecological Landscape Design: A Case Study Applying LEED Certification Criteria to BTU Mimar Sinan Campus - Onur, Aksoy; Erken, Kamıl (My University, 2024)
Ecological design is an approach that is applied in campus areas. This study aims to determine the LEED certificate points achievable through proposed ecological landscape designs for campus areas. The v3-2009 version of the LEED certificate was used in the study. In this study, national and international articles, LEED scoring system was first examined. Within the scope of the information obtained, the point value of the study area was calculated for its current form based on the LEED certification system. New ecological landscape design study was proposed for the area and re-scoring was performed within the scope of this proposed project. After the total score that campus would receive from the LEED certificate and the score obtained from each category were determined. Through the ecological campus planning approach developed in this study, the campus's certificate score increased from 10 to the 'Silver certificate' level, totalling 50 points.
Keywords: Planting design; ecological design; energy and water efficiency; green certification; LEED.